Factors Associated with Abdominal Obesity in the Productive Age in Surabaya - Fani Kusteviani (Universitas Airlangga, 2015)
Obesity has become a problem in the health and nutrition of the world community. Abdominal obesity is more at risk of developing health problems such as diabetes mellitus, metabolic syndrome, hypertension, and cardiovascular disease than general obesity. Behavioral and environmental factors also genetic factors play a role in the onset of abdominal obesity. The purpose of this study was to analyze the factors associated with abdominal obesity at a productive age (15-64 years) in the city of Surabaya. The independent variables used were age, sex, marital status, family size, education, occupation, smoking habits, physical activity, consumption of vegetables and or fruits, sweet foods or drinks, fatty foods, and mental-emotional conditions. This research is analytic with cross-sectional design. The study uses secondary data from the Indonesia basic health research (Riskesdas) at 2007. The population taken was respondents in the city of Surabaya with a total sample of 2191 respondents which selected using simple random sampling. Data were analyzed by the Chi-square test and logistic regression. The analysis showed that risk factors for abdominal obesity were age 35-64 years, female sex, marital or divorced status, had educated at lower or equal as senior high school level, and regular consumption of fatty foods. Increasing knowledge, physical activity, and reducing fatty foods can prevent abdominal obesity.